2017
DOI: 10.1002/app.46046
|View full text |Cite
|
Sign up to set email alerts
|

Wetting measurements as a tool to predict the thermoplastic/thermoset rubber compatibility in two‐component injection molding

Abstract: Recently a novel two-component injection molding process has been developed combining thermoplastics with thermoset rubbers. Since the adhesion strength between the two materials strongly depends on the combination of a specific thermoplastic and a thermoset rubber, there is a need to predict their compatibility, defined as the formation of a strong interface. In this study, the wetting behavior of molten thermoplastics on rubber substrates is used to predict their compatibility since wetting is an essential s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Consequently, physical interactions are enhanced between the rubber and thermoplastics as good wetting is a prerequisite for further adhesion mechanisms. A Dataphysics OCA 15 plus, equipped with a Dataphysics TEC 350 temperature control unit was used, which is the same set‐up as used by Bex et al . The calculation of the contact angles was executed with Dataphysics SCA 202 analysis software.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, physical interactions are enhanced between the rubber and thermoplastics as good wetting is a prerequisite for further adhesion mechanisms. A Dataphysics OCA 15 plus, equipped with a Dataphysics TEC 350 temperature control unit was used, which is the same set‐up as used by Bex et al . The calculation of the contact angles was executed with Dataphysics SCA 202 analysis software.…”
Section: Methodsmentioning
confidence: 99%
“…Then, a thermoplastic granulate was placed on the rubber substrate with the spherical side facing down. The temperature was set at 180, 200, and 230 °C, respectively for PP, PE, and PC . ABS was not tested as degradation occurred too fast even under N 2 environment in the available heating chamber.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work, the process development was described for realizing two‐component injection molding for rubbers with thermoplastics . In other work, the compatibility between specific rubbers with thermoplastics was demonstrated and techniques were presented to predict the compatibility . The aim of the present study is the optimization of the process settings by investigating the effect of the following parameters on the bond strength: mold temperature, injection temperature, holding pressure, injection speed, and surface roughness of the thermoplastic part at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…In 2K injection molding studies, the focus has mainly been on the influence of process parameters on the adhesion strength as already discussed by Bex et al [1,[3][4][5][6] Furthermore, material compatibility has been investigated to predict the adhesion in 2K injection molding. [7,8] Additionally, Laing et al [9] showed the importance of investigating the influence of EPDM composition on the adhesion with polar and non-polar thermoplastics. In that study, it was found that co-agent type and concentration at a fixed peroxide concentration significantly affect the adhesion strength and mechanism.…”
Section: Introductionmentioning
confidence: 99%